THE NEW CRIMINAL PROCEDURE CODE AND THE CRISIS OF DUE PROCESS OF LAW IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Dwijaya, Ananda Gymnastiar (Hukum Responsif, 2026)
The ratification of the New Criminal Code on November 18, 2025, which came into effect on January 2, 2026, marks a fundamental change in Indonesia's criminal procedure law system. This update is intended to address the evolution of modern crime and the demands of law enforcement effectiveness. However, the expansion of law enforcement officials' authority in the areas of detention, confiscation, search, and eavesdropping raises serious problems for the principle of due process of law. A number of studies show that weakening the principle of procedural justice can increase the risk of arbitrariness and human rights violations. This research aims to critically analyze the New Criminal Code from the perspective of the state of law and the protection of human rights. The research method used is normative juridical with a statutory and conceptual approach. The results of the study show that strengthening the authority of the apparatus, without balancing it with strengthening judicial control, has the potential to shift the balance between state power and citizens' rights in the criminal justice system.